2006
DOI: 10.1128/ec.5.2.411-421.2006
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Membrane Dynamics in the Filamentous Fungus Aspergillus oryzae

Abstract: Vacuoles in filamentous fungi are highly pleomorphic and some of them, e.g., tubular vacuoles, are implicated in intra-and intercellular transport. In this report, we isolated Aovam3, the homologue of the Saccharomyces cerevisiae VAM3 gene that encodes the vacuolar syntaxin, from Aspergillus oryzae. In yeast complementation analyses, the expression of Aovam3 restored the phenotypes of both ⌬vam3 and ⌬pep12 mutants, suggesting that AoVam3p is likely the vacuolar and/or endosomal syntaxin in A. oryzae. FM4-64 [N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 48 publications
9
85
1
Order By: Relevance
“…In the region before the first septum the vacuolar markers were abundant in an interconnected network of thin (Ͻ1 m) tubules, often with small, attached vesicles. These results with N. crassa are generally consistent with observations made using GFPtagged VAM-3 in Aspergillus oryzae (45,54). N. crassa grows faster, and the diameter of hyphae can be fivefold larger.…”
Section: Downloaded Fromsupporting
confidence: 80%
See 1 more Smart Citation
“…In the region before the first septum the vacuolar markers were abundant in an interconnected network of thin (Ͻ1 m) tubules, often with small, attached vesicles. These results with N. crassa are generally consistent with observations made using GFPtagged VAM-3 in Aspergillus oryzae (45,54). N. crassa grows faster, and the diameter of hyphae can be fivefold larger.…”
Section: Downloaded Fromsupporting
confidence: 80%
“…GFP and fluorescent dyes have been used successfully to examine nuclei and mitochondria (24,26). Several reports have shown that "the vacuole" is far more dynamic and complex than the textbook presentation of a large spherical organelle (10,24,31,33,54). Our understanding of the structure and abundance of the ER and the Golgi body is limited.…”
mentioning
confidence: 99%
“…We examined vacuolar morphology in the V o a mutants by staining live cells with FM4-64 and CMAC. Upon endocytosis, the lipophilic dye FM4-64 stains vacuolar membranes (46), whereas CMAC passively accumulates in the vacuolar lumen (47). Fig.…”
Section: Loss Of V-atpase V O a Isoforms Vph1p And Stv1p Separately Dmentioning
confidence: 99%
“…This functional relationship can also be seen in the filamentous fungus Aspergillus oryzae, where AoVam3p is the sole orthologue of both Sac. cerevisiae Vam3p and Pep12p (Shoji et al, 2006;Kuratsu et al, 2007). Furthermore, although Vsl1p is thought to be the counterpart of Vam7p as we elucidated here, Vsl1p has functional redundancy with Fsv1p.…”
Section: Discussionmentioning
confidence: 91%